2010
DOI: 10.1017/s002211201000042x
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear dynamics and synthetic-jet-based control of a canonical separated flow

Abstract: A novel flow configuration devised for investigation of active control of separated airfoil flows using synthetic jets is presented. The configuration consists of a flat plate, with an elliptic leading edge and a blunt trailing edge, at zero incidence in a free stream. Flow separation is induced on the upper surface of the airfoil at the aft-chord location by applying suction and blowing on the top boundary of the computational domain. Typical separated airfoil flows are generally characterized by at least thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 57 publications
(102 reference statements)
3
31
0
Order By: Relevance
“…For example in the experiments of Yarusevych et al 52 , for the range of Reynolds numbers for which reattachment occured, this ratio was at least 7. There is one study in which these two frequencies are similar, that of Kotapati et al 16 . The authors studied a flow configuration with laminar separation, reattachment and vortex shedding.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…For example in the experiments of Yarusevych et al 52 , for the range of Reynolds numbers for which reattachment occured, this ratio was at least 7. There is one study in which these two frequencies are similar, that of Kotapati et al 16 . The authors studied a flow configuration with laminar separation, reattachment and vortex shedding.…”
Section: Resultsmentioning
confidence: 94%
“…Their 2D simulations showed that the shear frequency and the shedding locked to a single frequency of 2.9, while we find locking at a larger frequency (equal to 4.5). The explanation for this difference is the following: the authors induced the separation bubble close to the trailing edge (the reattachment point is located at 0.97C), therefore the effective length scale for the vortex shedding (in essence, the effective thickness seen by the flow) is the sum of the plate thickness and the height of the separating bubble 16 (equal to 0.037C and located at around 0.88C, as can be observed from their figure 5). In our case the separation bubble appears in the middle of the airfoil, the flow reattaches at 0.56C, so the thickness of the bubble does not affect the effective length scale of shedding.…”
Section: Resultsmentioning
confidence: 99%
“…[28][29][30] The forcing frequency of the SJ is arguably the most important parameter and is indeed the key parameter to be optimized for better separation control effect. 24,[31][32][33] Experimental and numerical results 31,34,35 reveal that the fundamental mechanism of separation control by a SJ is the formation of coherent roll-up lifting vortices not far from the airfoil surface. Such vortices are also observed in the cases of a nominally 2D hump 17 and flat plate.…”
Section: Introductionmentioning
confidence: 99%
“…Various approaches have recently been developed for aircraft tracking control using SJAs (e.g., see [8,[10][11][12][13]), where the SJA actuator uncertainty is compensated using adaptive control methods or neural networks. Other popular approaches for SJA-based control are computational fluid dynamics-(CFD-) based numerical techniques (see [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]). Adaptive control, neural networkbased control, and numerical CFD methods have been shown to be effective in their respective SJA-based control tasks.…”
Section: Introductionmentioning
confidence: 99%